Unions, safety committees and workplace injuries - Reilly, Barry (1995)
Examines the determinants of workplace injuries for a sample of manufacturing establishments in the UK. Assesses the role played by union-appointed safety representatives and joint health and safety consultative committees in reducing the frequency of workplace accidents.